An Atypical Case of a Common Pregnancy Issue: Appendicitis-Like Hyperemesis Gravidarum - Janice Chung; Ryan P. Berryman (Case Reports in Medicine)
Hyperemesis gravidarum (HG) is a severe subtype of nausea and vomiting in pregnancy (NVP) that typically affects women in their first trimester of pregnancy. Because HG is a diagnosis of exclusion, a thorough work-up ruling out organic causes must be performed. Herein, we describe a case of a pregnant woman with HG who presented with intractable pain mimicking appendicitis. While her clinical picture and ultrasound findings were only mildly consistent with appendicitis, the only therapy that provided pain relief was empiric antibiotic treatment that was prescribed due to a mildly elevated procalcitonin of 0.61. Thereby, the detection and treatment of concurrent organic causes is important as it may provide significant symptomatic relief in cases of concurrent HG.